Balance between strength and ductility of dilute Fe2B by high-throughput first-principles calculations. Issue 4 (15th February 2021) - Wang, Guangchi; Jiang, Yehua; Li, Zulai; Chong, Xiaoyu; Feng, Jing
Abstract: In boride ceramics, Fe2 B typically functions as the primary wear-resistant phase owing to its high hardness, but the elastic and ductile-brittle properties of Fe2 B greatly influence its wear resistance and industrial application. First-principles calculations using density functional theory (DFT) were utilized to systematically investigate the effects of Al, Si, and transition elements (including 3d, 4d, and 5d transition elements) on the mechanical properties and electronic structure of Fe31 MB16 with a dilute solution model. The bulk modulus ( B ), shear modulus ( G ), and Young's modulus ( E ) were calculated through the stress-strain method. The Vickers hardness ( H V ) and fracture toughness ( K IC ) were calculated by semi-empirical models. The electronic structures and chemical bonding were analyzed using the charge density difference, electron localization function, and Mulliken bond population. Overall, Fe31 YB16 had the largest moduli ( B, G, and E ) among all the Fe31 MB16 compounds that were investigated, while Fe31 CrB16 had the highest hardness. Compared with pure Fe2 B, the ductility of Fe31 MB16 improved to varying degrees according to the B/G and Poisson's ratio ( σ ) criteria, respectively. However, adding alloying elements in this concentration did not change the intrinsic brittleness of Fe2 B. Moreover, the trends in the calculated K IC of Fe31 MB16 (M = Cr, Mn, Mo, and W respectively) were consistent with those of experiments. The electronic structure and Mulliken population analysis showed that the differences in the mechanical properties of the Fe31 MB16 compounds were primarily determined by the M-B and B–B bonds because the alloying element M replaced Fe. These results provide guidance for improving the ductility of Fe2 B and its industrial application.